European futures : challenges and crossroads for the European Union of 2050 - Damro, Chad, 1970-; Heins, Elke; Scott, Andrew, 1953- (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This edited volume explores the opportunities and challenges facing the European Union in the future from different disciplines and assesses the EU's prospects across various policy areas. Using the European Commission's 2017 White Paper presenting five different scenarios for the future of Europe to 2050 as an organising framework for analysis and debate, the volume reflects upon the drivers of the EU's future, including its changing place in an evolving world, a transformed economy and society, heightened threats and concerns about security and borders, and questions of trust and legitimacy. The concluding chapter summarises and compares the findings to determine which of the scenarios is the most instructive to understand and plan European Futures to 2050, and beyond. This book will be of key interest to scholars and students of European integration, EU Politics/Studies, and more broadly international relations, as well as European policy makers"--
Introduction : European futures, past and present / Chad Damro, Elke Heins and Drew Scott -- The EU capital market : 'carrying on' into the future? / Niamh Moloney -- European economic governance : past, present and future / Amy Verdun -- The future of EU social and labour market policy : between a European social union and an EU regulatory welfare state? / Caroline de la Porte -- Environment and climate 2050 : common purpose or constraining dissensus? / Charlotte Burns -- Normative, protective, transformative Europe : digital and climate meta-policies / Heather Grabbe -- Migration and the future of Europe / James Dennison and Andrew Geddes -- The future of EU trade policy in turbulent times / Maria Garcia -- EU foreign affairs and the future : multi-level opportunities vs. multi-layered risks / Amelia Hadfield -- Member state constellations and the 'future of Europe' debate / Simon Bulmer -- Towards a win-win package deal and more effective decision-making in a union faced with disruptive change / Johannes Greubel and Fabian Zuleeg -- The future of Europe : alternative scenarios / Brigid Laffan -- Conclusion : the future of European integration to 2050 across scenarios and policy areas / Elke Heins and Chad Damro.
OCLC-licensed vendor bibliographic record.
Keywords: European Union -- Forecasting; European cooperation -- Forecasting; Environmental policy -- European Union countries -- Forecasting; European Union countries -- Economic policy -- Forecasting; POLITICAL SCIENCE / General